Incidence Rate of Acute Encephalitis Syndrome without Specific Treatment in India and Nepal - Nagabhushana Rao Potharaju (Wolters Kluwer Medknow Publications, 2012)
Background: A performance target (PT) for the incidence rate (IR) of acute encephalitis syndrome (AES) was not defined by the World Health Organization (WHO) due to lack of data. There is no specific treatment for ~90% of the AES cases. Objectives: (1) To determine the IR of AES not having specific treatment (AESn) in two countries, India and Nepal. (2) To suggest the PT. Subjects and Methods: This was a record-based study of the entire population of India and Nepal from 1978 to 2011. The WHO definition was used for inclusion of cases. Cases that had specific treatment were excluded. IR was calculated per 100,000 population per annum. Forecast IR was generated from 2010 to 2013 using time-series analysis. Results: There were 165,461 cases from 1978 to 2011, of which 125,030 cases were from India and 40,431 were from Nepal. The mean IR of India was 0.42 (s 0.24) and that of Nepal was 5.23 (s 3.03). IRs of 2010 and 2011 of India and that of 2011 of Nepal were closer to the mean IR rather than the forecast IR. IR of 2010 of Nepal was closer to the forecast IR. The forecast IR for India for 2012 was 0.49 (0.19-1.06), for 2013 was 0.42 (0.15-0.97) and for Nepal for both 2012 and 2013 was 5.62 (1.53-15.05). Conclusions: IRs were considerably different for India and Nepal. Using the current mean IR as PT for the next year was simple and practical. Using forecasting was complex and, less frequently, useful.